2023
DOI: 10.1200/jco.2023.41.4_suppl.lba292
|View full text |Cite
|
Sign up to set email alerts
|

Zolbetuximab + mFOLFOX6 as first-line (1L) treatment for patients (pts) withclaudin-18.2+ (CLDN18.2+) / HER2− locally advanced (LA) unresectable or metastatic gastric or gastroesophageal junction (mG/GEJ) adenocarcinoma: Primary results from phase 3 SPOTLIGHT study

Abstract: LBA292 Background: 1L treatment for pts with HER2−, mG/GEJ adenocarcinoma is typically chemotherapy and immunotherapy; an unmet need still exists. CLDN18.2 is expressed in normal gastric mucosa cells and retained in mG/GEJ tumor cells. In the FAST study, zolbetuximab, which targets CLDN18.2, prolonged survival of pts with LA unresectable or mG/GEJ adenocarcinoma when combined with chemotherapy. SPOTLIGHT (NCT03504397) is a phase 3 global, double-blind study comparing zolbetuximab + folinic acid, 5-FU, and oxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 0 publications
11
67
0
3
Order By: Relevance
“…The SPOTLIGHT and the GLOW trial randomized patients when ≥75% of tumor cells showed moderate to strong membranous immunohistochemical staining [ 51 , 52 ]. First results of the SPOTLIGHT trial were presented at the 2023 ASCO GI Cancers Symposium and showed superior PFS (10.61 vs. 8.67 months; HR 0.751; 95% CI 0.589–0.942; p = 0.0066) as well as superior OS (18.23 vs. 15.54 months; HR 0.75; 95% CI 0.601–0.936); p = 0.0053) for FOLFOX + zolbetuximab in comparison to FOLFOX + placebo in advanced and metastatic patients [ 53 ]. These results represent a major breakthrough in targeted therapies for gastroesophageal cancer and may lead to further trials in resectable settings.…”
Section: Gastric Adenocarcinomamentioning
confidence: 99%
“…The SPOTLIGHT and the GLOW trial randomized patients when ≥75% of tumor cells showed moderate to strong membranous immunohistochemical staining [ 51 , 52 ]. First results of the SPOTLIGHT trial were presented at the 2023 ASCO GI Cancers Symposium and showed superior PFS (10.61 vs. 8.67 months; HR 0.751; 95% CI 0.589–0.942; p = 0.0066) as well as superior OS (18.23 vs. 15.54 months; HR 0.75; 95% CI 0.601–0.936); p = 0.0053) for FOLFOX + zolbetuximab in comparison to FOLFOX + placebo in advanced and metastatic patients [ 53 ]. These results represent a major breakthrough in targeted therapies for gastroesophageal cancer and may lead to further trials in resectable settings.…”
Section: Gastric Adenocarcinomamentioning
confidence: 99%
“…In the phase IIb FAST study, zolbetuximab + chemotherapy significantly improved survival compared with chemotherapy alone in AGC patients expressing CLDN18.2 [ 62 ]. The phase III SPOTLIGHT placebo-controlled trial of zolbetuximab + chemotherapy in 565 patients with CLDN18.2-positive, HER2-negative AGC showed that the combination was superior to chemotherapy + placebo for PFS and OS in all randomized patients (median PFS 10.61 vs 8.67 months, HR: 0.751; 95% CI: 0.589–0.942, p = 0.0066; median OS 18.23 vs 15.54 months, HR: 0.75; 95% CI: 0.601–0.936, p = 0.0053) [ 63 ]. Zolbetuximab is being investigated in combination with immunotherapeutic agents in the ILUSTRO trial in patients with CLDN18.2 positive AGC (NCT03505320).…”
Section: Anti-pd-1 Antibody Together With Claudin 182 (Cldn182)-targe...mentioning
confidence: 99%
“…Results were recently reported from the SPOTLIGHT trial, a double-blind placebo-controlled trial evaluating the addition of zolbetuximab to first-line chemotherapy with modified FOLFOX6 in advanced HER2-negative gastric and esophageal adenocarcinoma [13 ▪▪ ]. Patients had to test positive by immunohistochemistry for overexpression of CLDN 18.2, and high expression was detected in 42% of screened HER2-negative patients.…”
Section: Metastatic Esophagogastric Cancermentioning
confidence: 99%